Upwelling longwave irradiance at Chesapeake Light Station measured in the presence of an obstruction with the component summation technique - Fabbri, Bryan; Schuster, Gregory L; Denn, Fred M; Lin, Bing; Rutan, David A; Su, Wenying; Eitzen, Zachary A; Madigan Jr., James J; Arduini, Robert F; Loeb, Norman G (PANGAEA, 2025)
The CERES Ocean Validation Experiment (COVE) was an instrument suite located at the Chesapeake Light Station approximately 25 kilometers east of Virginia Beach, Virginia (36N, 75.7W). COVE provided surface verification for the Clouds and the Earth's Radiant Energy System (CERES) satellite measurements for 16 years. However, the large light station occupied approximately 15% of the field of view of the upwelling longwave flux measurement (LWup), so radiation from the structure artificially perturbed the measurements. Hence, we use data from multiple instruments that are not influenced by the structure to accurately obtain (LWup); we call this the longwave component summation technique. The instruments required for the component summation are an infrared radiation thermometer to measure sea surface temperature, a pyrgeometer to measure downwelling longwave irradiance, and an air temperature probe. We find a strong negative bias between the obstructed upwelling pyrgeometer measurements and the component summation LWup in the colder months, less so in the warmer months. The bias ranged from -6% to +5% over COVE from 2004-2013. These range of biases are larger than the Baseline Surface Radiation Network (BSRN) targeted uncertainties of 2% or 3 W/m² (whichever is greatest), indicating that the component summation technique provides a significant correction to standard BSRN protocols when an obstruction is present. This work documents how we determine the component summation LWup irradiances, demonstrates that the calculated values achieve a relative standard error of 0.6% and are within the 2% target uncertainty, and presents guidelines for implementing this methodology at other locations.